Growing sorghum in all day lengths - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Scientists at the International Crop Research Institute for the Semi-arid Tropics (ICRISAT) in India are busy improving six sorghum varieties from Nigeria so that they do not depend on specific periods of sunlight to produce grain. Technically...